Geotecnologias aplicadas na avaliação da vulnerabilidade ambiental antrópica e risco de lixiviação de agrotóxicos - Oliveira, Alessandra Cunha Lopes (2019)
Environmental vulnerability is related to the susceptibility of an area to suffering damages when subjected to a natural or anthropogenic action. The main objective of this research was to evaluate the anthropic environmental vulnerability in the Federal Institute of the Espírito Santo campus of Alegre. This analysis was performed through a mapping that classified the study area according to vulnerability classes through the ArcGIS® version 10.3 computational application. Based on the classification map of land use and occupation were selected the anthropogenic classes to the environment. Each polygon was edited and exported for application of the Fuzzy logic to the Euclidean distance of the matrix variables. The values of the intervals were reclassified to scale from 0 to 1 in order to perform the division of the grids obtained with the Gamma operator according to the degree of environmental vulnerability. In order to support this evaluation, the environmental vulnerability conflict in areas of permanent preservation (APP), the estimation of the leaching potential of pesticides for coffee cultivation and the evaluation of the water quality with physical and chemical analyzes were also carried out. The pasture and agriculture classes are expanding on campus and have potential to cause environmental impacts, a fact that points to the vulnerability assessment indicating that the area is predominantly in regions of high and high vulnerability. Of the total area for APP in the Ifes, 28.27% is in conflicting land use. The active principles with the greatest leaching potential were Sulfentrazone and Thiamethoxam. When evaluating the water quality, it can be observed that the landscape pond near the swine unit was polluted, with high concentrations of organic matter and nutrients, which causes the reduction of the dissolved oxygen concentration in the water